Hydrogen economy in India: A status review - Kar, Sanjay Kumar; Sinha, Akhoury Sudhir Kumar; Harichandan, Sidhartha; Bansal, Rohit; Balathanigaimani, Marriyappan Sivagnanam (Wiley interdisciplinary reviews. Energy and environment, 2023)
India's rapid population growth and steady industrialization mean that energy demand will grow in industry, transport, electricity, and cooling. Due to greenhouse gas emissions reduction targets, fossil fuels will be less preferred to meet energy demand and consumption. Significantly, the transport sector will move toward green fuel, including hydrogen. However, most hydrogen is now produced from fossil fuels through partial oxidation or steam reforming natural gas or coal gasification. This article examines the continuous progress of hydrogen regarding its production, storage, and commercialization in India. Given the versatility in nature, hydrogen shall play a crucial role in decarbonizing the Indian economy by 2050. India's hydrogen energy roadmap was envisioned for an operational hydrogen economy by 2020. The objectives of the hydrogen roadmap remained unfulfilled. We found that inadequate infrastructural developments, lack of proactive policies, insufficient investment in the hydrogen value chain, slow market readiness, and a shortage of public awareness have contributed to the hydrogen economy's derailment in India. The proposed National hydrogen energy mission aims to revive India's hydrogen economy. Stakeholders should focus on hydrogen research, development, value chain development, and hydrogen technology commercialization. This article is categorized under: Emerging Technologies > Hydrogen and Fuel Cells Human and Social Dimensions > Social Acceptance Policy and Economics > Energy Transitions India's renewed interest on hydrogen economy